THE METHODICAL APPROACH TO DETERMINE THE DIRECTIONS OF STRATEGIC CHANGES AT MACHINE-BUILDING ENTERPRISES (INNOVATIVE ECONOMY, 2020)
Yakovchuk A.M. THE METHODICAL APPROACH TO DETERMINE THE DIRECTIONS OF STRATEGIC CHANGES AT MACHINE-BUILDING ENTERPRISES Purpose. The aim of the article is the substantiation of the methodical approach to determining the level of strategic changes required by machine-building enterprises, using methods of multidimensional statistical analysis.Methodology of research. The following methods are used in the process of research: lexical and semantic, logical and terminological analysis – for studying the cognitive filling of the terms: "strategic stability of the enterprise", "level of strategic stability". Also, the method of multivariate statistical analysis is used to determine the recommended direction of change for machine-building enterprises on the basis of calculated coefficients of the level of strategic stability.Findings.  The current level of strategic stability of the machine-building enterprises in Rivne and the region is substantiated, on the basis of which the recommended direction of further changes is determined in the context of five possible options: sustainable development; prevention of organizational traps; upgrade to go to the next spiral of development; withdrawal from a crisis situation; conducting complete transformation.Originality. The scientific and methodological approach to determining the main direction of change at machine-building enterprises is improved, which, unlike existing ones, is based on the establishment of the current level of strategic stability of the enterprise in the context of four groups of indicative indicators: financial, economic, technological, social and client, and takes into account the potential of the industry's life cycle, the level of innovation development of the enterprise, its previous integration experience and the experience of overcoming previous organizational crises.Its application will make it possible to determine the relevant direction of change for the machine-building enterprise (from ensuring sustainable development to a complete transformation to the next cycle of life cycle) and to establish the necessary level of changes to the general strategy at five levels.Practical value. The proposed scientific and methodological approach allows to determine the current level of strategic stability of domestic machine-building enterprises and to substantiate the main direction of the level and nature of changes that should be introduced by machine-building enterprises in order to further ensure a high level of strategic stability.Key words: strategic stability; machine-building enterprise; cluster; direction of change; coefficient of strategic stability; level of changes in the current strategy.
Keywords: Key words; strategic stability; machine-building enterprise; cluster; direction of change; coefficient of strategic stability; level of changes in the current strategy.